Long-lasting anti-aging EVA film and preparation method thereof

By preparation of porous materials in the EVA glue film and loading anti -aging additives, combined with co -hydrolysis and contraction treatment of silicate and silicane coupling agents, the aging problem of EVA glue film under the action of light, heat, and oxygen It has achieved its long -term anti -aging effect.

CN117487470BActive Publication Date: 2025-01-28SUZHOU YISHENG OPTICAL MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311510608.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-14
Publication Date
2025-01-28
Estimated Expiration
2043-11-14

AI Technical Summary

Technical Problem

In application, the EVA film turns yellow by the action of light, heat and oxygen, and the transmittance decreases, resulting in a decrease in solar cell efficiency. It is difficult for the prior art to achieve its long-term anti-aging.

Method used

By preparing the porous materials of the pores, and the anti -aging additives such as ultraviolet absorbers, antioxidants and light stabilizers on the porous materials, combined with the co -hydrolysis and sync of silicate and silicane coupling agent, improve the porous materials The load capacity of the pore rate and the anti -aging aid to achieve the slow release effect.

Benefits of technology

Effectively delay the yellow change process of the EVA glue film, improve its anti -aging performance, greatly improve the protection of the protection, and solve the long -term anti -aging problem of the EVA glue film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117487470B_ABST
    Figure CN117487470B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of packaging adhesive films, and specifically relates to a long-lasting anti-aging EVA adhesive film and a preparation method thereof, comprising the following steps: step S1, preparation of a mesoporous porous material; step S2, preparation of a mesoporous porous material loaded with an anti-aging auxiliary agent; step S3, preparation of a long-lasting anti-aging EVA adhesive film; the long-lasting anti-aging EVA adhesive film and the preparation method thereof of the invention effectively improve the porosity of the porous material by adopting a method of co-hydrolysis and condensation of silicate and silane coupling agent and mesoporation treatment, while increasing the loading amount of the anti-aging auxiliary agent, the functional groups and polar groups on the silane coupling agent can also adsorb the auxiliary agent, thereby improving the overall slow-release effect, and the loading of the anti-aging auxiliary agent on the porous material also effectively delays the consumption rate of the corrosion inhibitor, greatly improves the protection time, and solves the long-lasting anti-aging problem of the EVA adhesive film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of packaging adhesive films, and particularly relates to a long-lasting anti-aging EVA adhesive film and a preparation method thereof. Background Art

[0002] Solar energy is clean, renewable, abundant and available all over the world. Almost all other known energy sources come directly or indirectly from solar energy. The Earth absorbs about 4×10 15 KWh is equivalent to about one-quarter of the total oil reserves on earth. In today's technologically advanced world, with the continuous progress of material science, the cost-effectiveness of solar energy materials is constantly improving. The use of solar energy will enable humans to achieve a more harmonious state in terms of environmental protection and energy utilization.

[0003] Solar cells are devices that convert solar radiation into electricity. They are a high-tech technology for the development and utilization of solar energy and a new type of special power source. The principle of solar power generation is to use the quantum effect of semiconductors such as silicon to directly convert the sun's visible light into electrical energy. However, if the silicon chip is directly exposed to the atmosphere, its photoelectric conversion function will decay, so the battery must be encapsulated.

[0004] EVA is the mainstream photovoltaic cell encapsulation film at present. It has the advantages of transparency, flexibility, good adhesion, high cost performance and good processability. EVA encapsulation film is actually a layer of hot melt adhesive in application. When the temperature reaches the appropriate temperature, EVA melts and flows, and adheres to the bonding surface. In the solar cell encapsulation component, the yellowing of EVA film due to the effects of light, heat and oxygen, the decrease in transmittance and the subsequent reduction in solar cell efficiency are the problems that the solar cell processing industry urgently needs to solve. The reason why EVA film turns yellow is affected by many factors, the two most important of which are the degradation and oxidation of EVA itself and the aging of EVA by ultraviolet rays. EVA encapsulation film will degrade outdoors due to the effects of heat and oxygen. Norman S. Allen and others studied thermal oxygen aging. The study found that the degradation of EVA mainly includes two steps: one is the reduction of acetic acid, and the other is oxidation and the breakage of the main chain. The degradation rate is faster in oxygen than in nitrogen. FJPern et al. also believed that the thermal stability of cross-linked EVA film would decrease in the presence of 02 and H20. At the same time, they conducted many accelerated aging tests (AET). 2 (This value was measured in Golden in August 1992 when the weather was clear) is the ultraviolet radiation energy of one sun. Various accelerated aging conditions were used to test the EVA encapsulation adhesive. The results showed that at 7.5 ultraviolet suns and a blackboard temperature of 85°C, the EVA gradually turned yellow-brown, and the yellow index change rate was 2-3×10 -2; 10 UV suns, blackboard temperature 145℃, EVA quickly turns dark brown, the yellow index change rate is 4.5-5.5×10 -2 ; Under 1.2 UV suns, blackboard temperature 60.65℃ or 80.85℃, EVA has no obvious color change, and the yellow index change rate is 2-6.5×10 -4 Therefore, how to effectively slow down the aging of EVA film is a key factor in inhibiting the yellowing of EVA film, and is also an important technological innovation to promote the development of EVA film and photovoltaic field. Summary of the invention

[0005] The invention provides a long-term anti-aging EVA film and a preparation method thereof, so as to solve the problem that the EVA film cannot have a long-term anti-aging effect.

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a long-lasting anti-aging EVA film, comprising the following steps: step S1, preparation of a mesoporous porous material, firstly ultrasonically dispersing the porous material in a solution of water and alcohol for 30-60 minutes, then adding a template, a pore expander, a catalyst, a silicate and a silane coupling agent, reacting at 40-60°C and a rotation speed of 200-500rpm for 5-8h, then filtering, washing and drying, and then calcining at 400-700°C for 4-10h to prepare a mesoporous porous material; step S2, preparation of a mesoporous porous material loaded with an anti-aging additive, adding the mesoporous porous material containing the anti-aging additive In an alcohol solution, the mixture is stirred at a speed of 50-200 rpm for 12-24 hours to allow the mesoporous porous material to fully load the anti-aging agent, and then filtered, washed, dried and set aside to prepare a mesoporous porous material loaded with an anti-aging agent; step S3, preparation of a long-lasting anti-aging EVA film, the cross-linking agent, the auxiliary cross-linking agent, the silane coupling agent and the EVA particles are mixed evenly, and then baked at 40-50°C for 8-24 hours, and then the baked particles are mixed evenly with the mesoporous porous material loaded with the anti-aging agent, and then the film is prepared by extrusion, granulation, and cast film forming; wherein the anti-aging agent includes a UV absorber, an antioxidant and a light stabilizer.

[0007] On the other hand, the present invention also provides a long-lasting anti-aging EVA film obtained by the preparation method as described above, the film comprising a mesoporous porous material loaded with an anti-aging agent; the anti-aging agent comprises an ultraviolet absorber, an antioxidant and a light stabilizer; the porous material is one or a combination of two or more of zeolite, molecular sieve, quartz sand, mesoporous silica and mesoporous carbon materials.

[0008] The beneficial effect of the present invention is that the long-lasting anti-aging EVA film and the preparation method thereof of the present invention effectively improve the porosity of the porous material by adopting the co-hydrolysis condensation and mesoporation treatment of silicate and silane coupling agent, and at the same time increase the loading amount of the anti-aging additive while allowing the functional groups and polar groups on the silane coupling agent to adsorb the additive, thereby improving the overall sustained release effect. In addition, the loading of the anti-aging additive on the porous material also effectively delays the consumption rate of the corrosion inhibitor, greatly improves the protection time, and solves the long-term anti-aging problem of the EVA film.

[0009] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practicing the present invention.

[0010] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0012] Figure 1 This is a SEM image of the zeolite of the long-lasting anti-aging EVA film of the present invention;

[0013] Figure 2 This is a SEM image of the long-lasting anti-aging EVA film of the present invention;

[0014] Figure 3 It is a nitrogen adsorption curve diagram of the long-lasting anti-aging EVA film of the present invention;

[0015] Figure 4 It is a corrosion inhibitor release curve diagram of the long-lasting anti-aging EVA film of the present invention. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] The invention provides a method for preparing a long-lasting anti-aging EVA film, comprising the following steps: step S1, preparing a mesoporous porous material, firstly ultrasonically dispersing the porous material in a water and alcohol solution for 30-60 minutes, then adding a template, a pore expanding agent, a catalyst, a silicate and a silane coupling agent, reacting at 40-60° C. and a rotation speed of 200-500 rpm for 5-8 hours, then filtering, washing and drying, and then calcining at 400-700° C. for 4-10 hours to prepare the mesoporous porous material.

[0018] In this embodiment, specifically, the mass fraction ratio of each component in step S1 is:

[0019] Porous material: 1-5 parts; alcohol: 70-90 parts; water: 10-30 parts; template: 0.1-1 parts; pore expander: 0.01-0.3 parts; catalyst: 0.01-0.1 parts; silicate: 0.5-2 parts; silane coupling agent: 0.1-0.5 parts.

[0020] In this embodiment, specifically, the porous material is one or a combination of two or more of zeolite, molecular sieve, quartz sand, mesoporous silica and mesoporous carbon materials.

[0021] In this embodiment, specifically, the alcohol is one or a combination of two or more of methanol, ethanol or propanol.

[0022] In this embodiment, optionally, the mass ratio of water to alcohol is 1-3:7-9.

[0023] In this embodiment, specifically, the template is one of cetyltrimethylammonium bromide (CTAB), cetyltrimethylammonium chloride (CTAC), pyrrolidine, ethylenediamine, n-butylamine or polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123).

[0024] In this embodiment, specifically, the pore expanding agent is one or a combination of two or more of mesitylene, polymethyl methacrylate, polystyrene and polytert-butyl methacrylate.

[0025] In this embodiment, specifically, the catalyst is one or a combination of two or more of sodium hydroxide, ammonia water, formic acid, acetic acid, hydrochloric acid or ammonium chloride.

[0026] In this embodiment, specifically, the silicate is one or a combination of two or more of tetraethyl orthosilicate, tetra(2-ethylhexyl) silicate or isopropyl silicate.

[0027] In this embodiment, specifically, the silane coupling agent is one of KH550, KH560, KH570, KH792 and DL602.

[0028] In this embodiment, specifically, the washing method is rinsing with ethanol for 3 times, and the drying method is baking in an oven at 60° C. for 12 hours.

[0029] In this embodiment, specifically, step S2, preparation of a mesoporous porous material loaded with an anti-aging agent, adding the mesoporous porous material to an alcohol solution containing the anti-aging agent, stirring at a rotation speed of 50-200 rpm for 12-24 hours to allow the mesoporous porous material to fully load the anti-aging agent, then filtering, washing, drying, and setting aside to obtain a mesoporous porous material loaded with an anti-aging agent.

[0030] like Figure 1 As shown, the left side is the initial zeolite, the middle is the mesoporous zeolite, and the right side is the mesoporous zeolite loaded with corrosion inhibitor.

[0031] In this embodiment, specifically, the mass fraction ratio of each component in step S2 is:

[0032] Mesoporous porous material: 1-10 parts; alcohol: 100 parts; ultraviolet absorber: 5-10 parts; antioxidant: 5-10 parts; light stabilizer: 5-10 parts.

[0033] In this embodiment, specifically, the ultraviolet absorber is any one of a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber or a triazine ultraviolet absorber.

[0034] In this embodiment, specifically, the light stabilizer is any one of a light shielding agent light stabilizer, a quencher light stabilizer, a free radical scavenger light stabilizer, and a hydroperoxide decomposer light stabilizer.

[0035] In this embodiment, specifically, the antioxidant is any one of a hindered phenol antioxidant, an aromatic amine antioxidant, a phosphite antioxidant, a thioether antioxidant, and a metal passivator antioxidant.

[0036] In this embodiment, specifically, the alcohol solution is one or a combination of two or more of methanol, ethanol or propanol.

[0037] In this embodiment, specifically, the washing method is rinsing with ethanol for 3 times, and the drying method is baking in an oven at 80° C. for 24 hours.

[0038] In this embodiment, specifically, step S3, the preparation of long-lasting anti-aging EVA film, the cross-linking agent, the auxiliary cross-linking agent, the silane coupling agent and the EVA particles are mixed evenly, and then baked at 40-50°C for 8-24h, and then the baked particles are mixed evenly with the mesoporous porous material loaded with the anti-aging auxiliary agent, and then the film is prepared by extrusion, granulation, and cast film forming; wherein the anti-aging auxiliary agent includes a UV absorber, an antioxidant and a light stabilizer.

[0039] like Figure 2 As shown, the left side is the SEM image of pure EVA film, and the right side is the SEM image of EVA film containing mesoporous zeolite loaded with corrosion inhibitor. It can be seen that there is a clear distribution of white spots.

[0040] In this embodiment, specifically, the mass fraction ratio of each component in step S3 is:

[0041] EVA particles: 100 parts; mesoporous porous material loaded with anti-aging additives: 0.5-2 parts; cross-linking agent: 1-4 parts; auxiliary cross-linking agent: 0.1-1 parts; silane coupling agent: 1-4 parts; UV absorber: 0-2 parts; antioxidant: 0-2 parts; light stabilizer: 0-1 parts.

[0042] In this embodiment, specifically, the cross-linking agent is any one or more combinations of dibenzoyl peroxide, diisopropylbenzene peroxide, tert-butyl peroxide 2-ethylhexyl carbonate, 1,1-di-tert-butyl peroxide cyclohexane, tert-amyl peroxide 2-ethylhexyl carbonate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, di(4-methylbenzoyl) peroxide or peroxide-3,5,5-trimethylhexanoic acid tert-butyl ester.

[0043] In this embodiment, specifically, the auxiliary cross-linking agent is any one or more combinations of ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane triacrylate, triallyl isocyanurate or triallyl cyanurate.

[0044] In this embodiment, specifically, the silane coupling agent is any one or more combinations of KH550, KH560, KH570, KH792 or DL602.

[0045] like Figure 3 As shown, the greater the porosity, the greater the adsorption amount. At the same time, mesoporation can increase the porosity of zeolite, and the loading of corrosion inhibitor can be filled into the pores to reduce the porosity.

[0046] like Figure 4 As shown, the sustained release effect and adsorption capacity of mesoporous zeolite are better than those of untreated zeolite.

[0047] Tensile properties test:

[0048] Initial mechanical properties: tested according to GB / T1040.3-2006, with a tensile rate of 500 mm / min.

[0049] Mechanical properties after aging: PCT48h (121℃, 0.2MPa, 48h), then tested according to GB / T1040.3-2006, with a tensile rate of 500mm / min.

[0050] Yellowing test:

[0051] UV aging test:

[0052] Sample preparation process: Take two pieces of EVA film with a size of 300mm×150mm, and stack them from bottom to top in the order of front plate material, front layer EVA film, back layer EVA film, and back plate material. Put the front plate downward into the vacuum laminator, and laminate according to the temperature and time required by the product to obtain a laminate sample with no defects in appearance. The cross-linking degree of the cross-linked EVA film is required to reach more than 60%. Prepare 3 laminate samples.

[0053] Testing process:

[0054] 1) Place the glass surface of the sample toward the light source and place it in the effective irradiation area of ​​the UV aging test chamber. Test conditions: a) UV spectrum distribution: The irradiation intensity between the wavelength of 280nm and 400nm is 50W / m 2 ~150W / m 2 , the uniformity of illumination on the test sample surface is within 15%. The irradiation in the 280nm to 320nm band accounts for 3% to 10% of the total irradiation;

[0055] b) During UV irradiation, the surface temperature of the sample in the test chamber is maintained at 60℃±5℃;

[0056] c) Accumulation of irradiation power: Accumulate the actual amount of radiation received by the sample surface and calibrate the UV power regularly.

[0057] 2) Test time: based on the cumulative dose of irradiation power, generally 120kWh / m 2 .

[0058] 3) After the test, take out the sample and restore it in an open environment at 23℃±5℃ and relative humidity less than 75% for 2-4 hours;

[0059] 4) The yellowness index of the laminate samples before and after the test was measured according to ASTM E313-2010. Each sample was measured at no less than 3 points. The yellowness index of the sample was the average value of the measured points, and the difference in the yellowness index before and after aging was recorded.

[0060] Damp heat aging test:

[0061] 1) Place all samples in a high temperature and high humidity aging test chamber and set the test conditions: temperature 85℃±2℃, relative humidity 85%±5%;

[0062] 2) The test time is 1000 hours. After the test, the sample is taken out and restored in an open environment at 23℃±5℃ and relative humidity less than 75% for 2-4 hours;

[0063] 3) The yellowness index of the laminate samples before and after the test was measured according to ASTM E313-2010. Each sample was measured at no less than 3 points. The yellowness index of the sample was the average value of the measured points, and the difference in the yellowness index before and after aging was recorded.

[0064] The microstructure and morphology of the sample in the present invention are detected and observed by scanning electron microscopy (SEM); the porosity of the mesoporous porous material is determined by nitrogen adsorption experiment; and the slow-release effect of the loaded corrosion inhibitor is tested by ultraviolet spectrophotometer at 200-400nm.

[0065] Example 1

[0066] The first step is the preparation of mesoporous porous materials:

[0067] First, the zeolite was ultrasonically dispersed in a solution of water and ethanol for 60 minutes, and then CTAB, mesitylene, sodium hydroxide, tetraethyl orthosilicate and KH570 were added, and the reaction was carried out at 40°C and 500 rpm for 5 hours, and then filtered, washed with ethanol for 3 times, dried in an oven at 60°C, and then calcined at 400°C for 8 hours. The mass ratio of each component is as follows:

[0068]

[0069] In the second step, the ultraviolet absorber, antioxidant and light stabilizer are dispersed in the alcohol solution, and then the mesoporous porous material obtained in the first step is added to the dispersion, and stirred at a speed of 200 rpm for 12 hours to allow the mesoporous porous material to fully load the anti-aging additives, and then filtered, rinsed with ethanol twice, and dried at 80°C for 24 hours for use. The mass ratio of each component is as follows:

[0070]

[0071]

[0072] In the third step, the crosslinking agent, auxiliary crosslinking agent, silane coupling agent and EVA particles are mixed evenly, and then baked at 40°C for 24 hours. After that, the baked particles are mixed evenly with the mesoporous porous material loaded with anti-aging additives obtained in the second step, and then the film is prepared by extrusion, granulation, and casting. The processing temperature is 60°C. The mass ratio of each component is as follows:

[0073]

[0074] Example 2

[0075] The first step is the preparation of mesoporous porous materials:

[0076] First, the molecular sieve was ultrasonically dispersed in a solution of water and methanol for 30 minutes, and then CTAC, polymethyl methacrylate, ammonia, tetra(2-ethylhexyl) silicate and DL602 were added, and the reaction was carried out at 60°C and 200rpm for 8 hours, and then filtered, washed with ethanol for 3 times, dried in an oven at 60°C, and then calcined at 700°C for 4 hours. The mass ratio of each component is as follows:

[0077]

[0078]

[0079] In the second step, the ultraviolet absorber, antioxidant and light stabilizer are dispersed in the alcohol solution, and then the mesoporous porous material obtained in the first step is added to the dispersion, and stirred at a speed of 50 rpm for 24 hours to allow the mesoporous porous material to fully load the anti-aging additives, and then filtered, rinsed with ethanol twice, and dried at 80°C for 24 hours for use. The mass ratio of each component is as follows:

[0080]

[0081] Preferably, the ultraviolet absorber is a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber or a triazine ultraviolet absorber.

[0082] In the third step, the crosslinking agent, auxiliary crosslinking agent, silane coupling agent and EVA particles are mixed evenly, and then baked at 50°C for 8 hours. After that, the baked particles are mixed evenly with the mesoporous porous material loaded with anti-aging additives obtained in the second step, and then the film is prepared by extrusion, granulation, and casting. The processing temperature is 110°C. The mass ratio of each component is as follows:

[0083]

[0084] Example 3

[0085] The first step is the preparation of mesoporous porous materials:

[0086] First, quartz sand was ultrasonically dispersed in a solution of water, methanol and ethanol for 50 minutes, and then ethylenediamine, mesitylene, polystyrene, acetic acid, tetraethyl orthosilicate and KH560 were added, and the mixture was reacted at 50°C and 400 rpm for 7 hours, and then filtered, washed with ethanol for 3 times, dried in an oven at 60°C, and calcined at 500°C for 6 hours. The mass proportions of the components are as follows:

[0087]

[0088] In the second step, the ultraviolet absorber, antioxidant and light stabilizer are dispersed in an alcohol solution, and then the mesoporous porous material obtained in the first step is added to the dispersion, and stirred at a speed of 100 rpm for 18 hours to allow the mesoporous porous material to fully load the anti-aging additives, and then filtered, rinsed with ethanol twice, and dried at 80°C for 24 hours for use. The mass ratio of each component is as follows:

[0089]

[0090] In the third step, the crosslinking agent, auxiliary crosslinking agent, silane coupling agent and EVA particles are mixed evenly, and then baked at 50°C for 12 hours. After that, the baked particles are mixed evenly with the mesoporous porous material loaded with anti-aging additives obtained in the second step, and then the film is prepared by extrusion, granulation, and casting. The processing temperature is 90°C. The mass ratio of each component is as follows:

[0091]

[0092] Example 4

[0093] The first step is the preparation of mesoporous porous materials:

[0094] First, mesoporous silica was ultrasonically dispersed in a solution of water and ethanol for 40 minutes, and then P123, mesitylene, acetic acid, formic acid, tetraethyl orthosilicate, isopropyl silicate and KH792 were added, and the mixture was reacted at 50°C and 300 rpm for 6 hours, and then filtered, washed with ethanol for 3 times, dried in an oven at 60°C, and calcined at 600°C for 7 hours. The mass ratio of each component is as follows:

[0095]

[0096]

[0097] In the second step, the ultraviolet absorber, antioxidant and light stabilizer are dispersed in an alcohol solution, and then the mesoporous porous material obtained in the first step is added to the dispersion, and stirred at a speed of 100 rpm for 18 hours to allow the mesoporous porous material to fully load the anti-aging additives, and then filtered, rinsed with ethanol twice, and dried at 80°C for 24 hours for use. The mass ratio of each component is as follows:

[0098]

[0099] In the third step, the crosslinking agent, auxiliary crosslinking agent, silane coupling agent and EVA particles are mixed evenly, and then baked at 50°C for 12 hours. After that, the baked particles are mixed evenly with the mesoporous porous material loaded with anti-aging additives obtained in the second step, and then the film is prepared by extrusion, granulation, and casting. The processing temperature is 90°C. The mass ratio of each component is as follows:

[0100]

[0101] Example 5

[0102] First, zeolite and quartz sand were ultrasonically dispersed in a solution of water and ethanol for 50 minutes, and then CTAB, mesitylene, sodium hydroxide, tetraethyl orthosilicate and KH570 were added, and the mixture was reacted at 50°C and 500 rpm for 5 hours, and then filtered, washed with ethanol for 3 times, dried in an oven at 60°C, and calcined at 400°C for 10 hours. The mass proportions of the components are as follows:

[0103]

[0104] In the second step, the ultraviolet absorber, antioxidant and light stabilizer are dispersed in an alcohol solution, and then the mesoporous porous material obtained in the first step is added to the dispersion, and stirred at a speed of 150 rpm for 22 hours to allow the mesoporous porous material to fully load the anti-aging additives, and then filtered, rinsed with ethanol twice, and dried at 80°C for 24 hours for use. The mass ratio of each component is as follows:

[0105]

[0106] In the third step, the crosslinking agent, auxiliary crosslinking agent, silane coupling agent and EVA particles are mixed evenly, and then baked at 50°C for 12 hours. After that, the baked particles are mixed evenly with the mesoporous porous material loaded with anti-aging additives obtained in the second step, and then the film is prepared by extrusion, granulation, and casting. The processing temperature is 90°C. The mass ratio of each component is as follows:

[0107]

[0108] Comparative Example 1

[0109] The particles obtained by uniformly mixing the crosslinking agent, the auxiliary crosslinking agent, the silane coupling agent and the EVA particles in Example 5 were cast into a film.

[0110] Comparative Example 2

[0111] The particles obtained by uniformly mixing the crosslinking agent, the auxiliary crosslinking agent, the silane coupling agent and the EVA particles in Example 5 are blended with the anti-aging auxiliary agent and cast into a film. The mass proportions are as follows:

[0112]

[0113] Comparative Example 3

[0114] Disperse the ultraviolet absorber, antioxidant and light stabilizer in an alcohol solution, then add the zeolite in Example 1 to the dispersion, stir at 200 rpm for 12 hours to fully load the anti-aging additive, then filter, rinse with ethanol twice, dry at 80°C for 24 hours, and set aside. The mass ratio of each component is as follows:

[0115]

[0116] In the third step, the crosslinking agent, auxiliary crosslinking agent, silane coupling agent and EVA particles are mixed evenly, and then baked at 40°C for 24 hours. After that, the baked particles are mixed evenly with the zeolite loaded with anti-aging additive obtained in the second step, and then the film is prepared by extrusion, granulation, and casting. The processing temperature is 60°C. The mass ratio of each component is as follows:

[0117]

[0118]

[0119] From the above examples and comparative examples, it can be seen that the method of loading anti-aging agents for sustained release can effectively delay the yellowing of EVA films, and the mesoporous modification of the present invention can more effectively improve this effect. The results of Examples 4 and 5 show that the improvement effect of adding additional anti-aging agents is limited, mainly because the anti-aging agents have been decomposed or lost in the early stage.

[0120] In summary, the long-lasting anti-aging EVA film and preparation method thereof of the present invention effectively improve the porosity of the porous material by adopting the co-hydrolysis condensation and mesoporation treatment of silicate and silane coupling agent, and while increasing the loading amount of the anti-aging additive, it also allows the functional groups and polar groups on the silane coupling agent to adsorb the additive, thereby improving the overall sustained release effect. In addition, the loading of the anti-aging additive on the porous material also effectively slows down the consumption rate of the corrosion inhibitor, greatly improves the protection time, and solves the long-term anti-aging problem of the EVA film.

[0121] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a long-lasting anti-aging EVA film, characterized in that: The steps include: Step S1, preparation of mesoporous porous material, firstly ultrasonically disperse the porous material in a solution of water and alcohol for 30-60 minutes, then add a template, a pore expander, a catalyst, a silicate and a silane coupling agent, react at 40-60° C. and a rotation speed of 200-500 rpm for 5-8 hours, then filter, wash and dry, and then calcine at 400-700° C. for 4-10 hours to prepare a mesoporous porous material; Step S2, preparation of a mesoporous porous material loaded with an anti-aging agent, adding the mesoporous porous material to an alcohol solution containing the anti-aging agent, stirring at a speed of 50-200 rpm for 12-24 hours to allow the mesoporous porous material to fully load the anti-aging agent, then filtering, washing, drying, and setting aside to obtain a mesoporous porous material loaded with an anti-aging agent; Step S3, preparation of long-lasting anti-aging EVA film, mixing the crosslinking agent, auxiliary crosslinking agent, silane coupling agent and EVA particles evenly, and then baking at 40-50°C for 8-24h, then mixing the baked particles evenly with the mesoporous porous material loaded with the anti-aging auxiliary agent, and then preparing the film by extrusion, granulation, and casting; wherein The anti-aging aids include ultraviolet absorbers, antioxidants and light stabilizers; The mass fraction ratio of each component in step S1 is: Porous materials: 1-5 parts; Alcohol: 70-90 parts; Water: 10-30 parts; Template: 0.1-1 part; Pore ​​expanding agent: 0.01-0.3 parts; Catalyst: 0.01-0.1 part; Silicate: 0.5-2 parts; Silane coupling agent: 0.1-0.5 parts; The mass fraction ratio of each component in step S2 is: Mesoporous porous material: 1-10 parts; Alcohol: 100 parts; UV absorber: 5-10 parts; Antioxidant: 5-10 parts; Light stabilizer: 5-10 parts; The mass fraction ratio of each component in step S3 is: EVA particles: 100 parts; Mesoporous porous material loaded with anti-aging additive: 0.5-2 parts; Cross-linking agent: 1-4 parts; Cross-linking agent: 0.1-1 part; Silane coupling agent: 1-4 parts; UV absorption: 0-2 parts; Antioxidant: 0-2 parts; Light stabilizer: 0-1 part.

2. The preparation method according to claim 1, characterized in that The porous material is one or a combination of two or more of zeolite, molecular sieve, quartz sand, mesoporous silica and mesoporous carbon materials.

3. The preparation method according to claim 1, characterized in that: The alcohol is one of methanol, ethanol or propanol or a combination of two or more thereof.

4. The preparation method according to claim 1, characterized in that: The template agent is one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, pyrrolidine, ethylenediamine, n-butylamine or polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.

5. The preparation method according to claim 1, characterized in that: The pore expanding agent is one or a combination of two or more of mesitylene, polymethyl methacrylate, polystyrene and polytert-butyl methacrylate.

6. The preparation method according to claim 1, characterized in that: The catalyst is one or a combination of two or more of sodium hydroxide, ammonia water, formic acid, acetic acid, hydrochloric acid or ammonium chloride.

7. The preparation method according to claim 1, characterized in that: The silicate is one or a combination of two or more of tetraethyl orthosilicate, tetra(2-ethylhexyl) silicate or isopropyl silicate.

8. The preparation method according to claim 1, characterized in that: The silane coupling agent is one of KH550, KH560, KH570, KH792 and DL602.

9. A long-lasting anti-aging EVA film obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The adhesive film includes a mesoporous porous material loaded with an anti-aging additive; The anti-aging aids include ultraviolet absorbers, antioxidants and light stabilizers; the porous material is one or a combination of two or more of zeolite, molecular sieve, quartz sand, mesoporous silica and mesoporous carbon materials.

Citation Information

Patent Citations

  • Preparation of mesoporous hollow SiO2 nano-material

    CN107285324A

  • Mesoporous silica, carboxylated mesoporous silica, drug loading system and preparation methods and application thereof mesoporous silica, carboxylated mesoporous silica and drug loading system

    CN113184861A

  • Photovoltaic adhesive film with low additive migration as well as preparation method and application of photovoltaic adhesive film

    CN117025133A